Volume uncertainty of (7) Iris shape models from disc-resolved images. Issue 3 (14th October 2020) - Dudziński, G; Podlewska-Gaca, E; Bartczak, P; Benseguane, S; Ferrais, M; Jorda, L; Hanuš, J; Vernazza, P; Rambaux, N; Carry, B; Marchis, F; Marsset, M; et al.
ABSTRACT: High angular resolution disc-resolved images of (7) Iris collected by VLT/SPHERE instrument are allowed for the detailed shape modelling of this large asteroid revealing its surface features. If (7) Iris did not suffer any events catastrophic enough to disrupt the body (which is very likely) by studying its topography, we might get insights into the early Solar system's collisional history. When it comes to internal structure and composition, thoroughly assessing the volume and density uncertainties is necessary. In this work, we propose a method of uncertainty calculation of asteroid shape models based on light curve and adaptive optics (AO) images. We apply this method on four models of (7) Iris produced from independent Shaping Asteroids using Genetic Evolution and All-Data Asteroid Modelling inversion techniques and multiresolution photoclinometry by deformation. Obtained diameter uncertainties stem from both the observations from which the models were scaled and the models themselves. We show that despite the availability of high-resolution AO images, the volume and density of (7) Iris have substantial error bars that were underestimated in the previous studies.